Kinetics and specificity of paternal mitochondrial elimination in Caenorhabditis elegans - Yang Wang (Nature Portfolio, 2016)
Autophagy mediates the degradation of paternal mitochondria after fertilization in C. elegansto ensure that mitochondria are inherited maternally. Here the authors show that mitochondrial dynamics is critical for the selectivity and kinetics of paternal mitochondrial elimination.